THE EFFECT OF PEER-ASSISTED LEARNING ON MEDICAL LABORATORY SCIENCE STUDENTS’ ACHIEVEMENT - Gafar Osman, Sahar Elderdiri; Basheir Abukaraig, Egbal Ahmed; Ahmed Elsheikh, Nasr Mohamed; Ali Alameen, Mohammed Albagir; Mohammed Ahmed, Ehab Mohammed Elmadenah; Mohammed Ahmed, Albara Abdulfatah; Almahi, Osman Mohammed (International Journal of Research -GRANTHAALAYAH, 2022)
Background: There was an urgent need for peer-assisted learning in the medical laboratory science program following examination failure in hematology, microbiology, and parasitology courses. Aim: The present study aimed to explore the effect of peers in supporting the low achiever medical laboratory science students at Alfajr College for Science and Technology. Methods: An experimental study was conducted at the medical laboratory science program. According to final exam results for the end-of-semester three all low achiever students in hematology [N=76/124 (61%)], microbiology [N=61/124 (49%)], parasitology [N=54/124 (48%)] and chemical pathology [N= 55/125 (36%)] courses assigned to peer-assisted learning groups by high achiever students (senior) under the lecturers’ supervision. The results of the end-of-semester four were compared to the end-of- semester three exam results, and the differences in achievement were measured. Results: Students’ achievements were significantly higher in the semester four final exam in parasitology, hematology, microbiology, and chemical pathology courses (P. value=<0.001; <0.001, <0.001 and <0.001), respectively. No significant differences in the histopathology course (P. value= 0.511). On the other hand, the achievement of high achiever students was significantly improved in parasitology (P. value= 0.006), while in microbiology and hematology courses was not (P. value= 0.046, and <0.001) respectively. Conclusions: Peer-assisted learning significantly positively affects low-achiever students. However, further research into peer-assisted learning on high-achievers as supporter students’ is required.